Immobilizing water-soluble dendritic electron donors and electron acceptors - Phthalocyanines and perylenediimides - Onto single wall carbon nanotubes - Hahn, Uwe; Engmann, Sarah; Oelsner, Christian; Ehli, Christian; Guldi, Dirk Michael; Torres, Tomas (Journal of the American Chemical Society, 2010)
The complementary use of spectroscopy and microscopy sheds light onto mutual interactions between semiconducting single wall carbon nanotubes (SWNT) and either a strong dendritic electron acceptor - perylenediimide - or a strong dendritic electron donor - phthalocyanine. Importantly, the stability of the perylenediimide/SWNT electron donor-acceptor hybrids decreases with increasing dendrimer generation. Two effects are thought to be responsible for this trend. With increasing dendrimer generation we enhance (i) the hydrophilicity and (ii) the bulkiness of the resulting perylenediimides. Both effects are synergetic and, in turn, lower the immobilization strength onto SWNT. Owing to the larger size of the phthalocyanines, phthalocyanine/SWNT electron donor-acceptor hybrids, on the other hand, did not reveal such a marked dependence on the dendrimer generation. Several spectroscopies confirmed that distinct ground- and excited-state interactions prevail and that kinetically and spectroscopically well-characterized radical ion pair states are formed within a few picoseconds. © 2010 American Chemical Society.